Desenvolvimento do pensamento algébrico de jovens crianças: potencialidades da exploração de padrões no contexto do ensino exploratório da Matemática - Alves, Beatriz (2019)
This study, developed as Design Research, examines the extent to which working with pattern can contribute to the development of algebraic thinking of young students. In order to do this, we conceived a teaching experience using repetition patterns that we made with a group of students of six years old, following the exploratory teaching of Mathematics. We conclude that working with patterns supports the development of algebraic thinking, favoring the establishment of relationships between variables and the use of symbols. However, the possibility of generalization is influenced by the characteristics of the pattern relative to the complexity of the motif. We underline the importance of the methodology of work in the classroom, especially the focus on communication by the students, supported by an inquiring dialogue.